2015
DOI: 10.1111/ced.12736
|View full text |Cite
|
Sign up to set email alerts
|

microRNA profiling for early detection of nonmelanoma skin cancer

Abstract: Our study suggests that the miRNAs with significant changes in expression (miR-19a-3p, miR-25-3p, miR-30a-5p, miR-145-5p and miR-186-5p) could serve as novel noninvasive biomarkers for detection of NMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Expression of miR-186-5p has only been reported in two studies, one on head & neck squamous cell carcinoma and another on non-melanoma skin cancer [11,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of miR-186-5p has only been reported in two studies, one on head & neck squamous cell carcinoma and another on non-melanoma skin cancer [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-186-5p was associated with poor prognosis of patients with head and neck squamous cell carcinoma [15]. In this study, we noted that overexpression of miR-186-5p in colorectal cancer was correlated with distant metastasis and lymphovascular permeation The prognosis of patients with colorectal cancer depends on the TNM pathological staging, which is a collective assessment of cancer invasion, lymph node and distant metastasis [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, analysis of circulating miRNA expression levels can be potentially employed for use in a noninvasive biomarker test for NMSC. Plasma profiling for early detection of NMSC has been explored in one recent study, which showed significant changes in expression of miRNA-19a, miRNA-25, miRNA-30a, miRNA-145, miRNA-186 [108]. While these are interesting findings, extensive validation of the clinical utility of these miRNAs as NMSC biomarkers is required.…”
Section: Rna Markersmentioning
confidence: 99%